Ordem política em Herman Dooyeweerd - Paz, Anderson Barbosa (2022)
Herman Dooyeweerd (1894-1977) was a Dutch philosopher who, in dialogue with German philosophy and neo-Calvinist thought, developed an original reflection on the laws and order of the cosmos. Dooyeweerd's philosophy is known as " Philosophy of the Law-Idea " or "Philosophy of the Cosmonomic Idea". From his modal theory – which identifies fifteen ontic aspects in which concrete things, events, relationships and social spheres function or exist – Dooyeweerd developed a political-social philosophy critical to individualist and universalist social theories. The problem of the present research is: what theoretical object characterizes the social-political philosophy of Herman Dooyeweerd? The research hypothesis is that the dooyeweerdian socio-political concern refers to the “problem of order”, i.e., the theoretical identification of the socio-political order within the limits of divine transcendental norms. The objective is to analyze Herman Dooyeweerd's conception of the political-social order. It is argued that Dooyeweerd's political philosophy neither is nor is concerned in being communitarian. Herman Dooyeweerd's interest is to theoretically apprehend, from the analysis of the structure of modes of experience, what are the principles, structures, functions and nature of things, events, relationships and social spheres. Dooyeweerd seeks to understand the typical structure of each social relationship, in order to understand the principles of a plural and harmonious political ordering. It is concluded that the concern of Herman Dooyeweerd's socio-political philosophy is the understanding of order within the cosmonomic parameters of divine creation.